PELAYANAN PRIMA FAKULTAS ILMU SOSIAL (FIS) UNNES DALAM BIDANG AKADEMIK DAN KEMAHASISWAAN - Handoyo, Eko (Faculty of Social Science, Universitas Negeri Semarang, 2009)
The problems to be solved in this study are: (1) The types of academic and student servicesÃ‚Â are provided by the Social Sciences Faculty?, (2) how far principles of public service pinsipÃ‚Â applied in the Social Sciences Faculty provides academic and student services?, ( 3) SejaumanakahÃ‚Â academic and student services are organized Social Sciences Faculty is based on the StandardÃ‚Â Public Service?, (4) How big is the level of customer satisfaction (students, stakehoulder, andÃ‚Â communities) to academic and student services provided by the Social Sciences Faculty?. TheÃ‚Â purpose of this research is to solve the problems mentioned above.This research took the location of the Social Sciences Faculty, especially in the areas ofÃ‚Â student services at Ã‚Â the 2nd foor of Building C7. Object of Ã‚Â this Ã‚Â research Ã‚Â is excellent serviceÃ‚Â performance demonstrated by the Social Sciences Faculty (FIS) Unit of analysis is the study ofÃ‚Â service providers implementing academic and student who coordinated the FIS and the Head ofÃ‚Â the TU leadership ranks of the faculty involved. The things that will be examined and dianalisÃ‚Â in this study are: (1) the forms of academic services (booking courses, KRS printing, etc.),Ã‚Â (2) application of the principles of public service organized by the Social Sciences Faculty ,Ã‚Â (3) application of public service standards in the service of academic and student affairs, (4)Ã‚Â measuring the level of customer satisfaction (students and other stakehoulder) for academic andÃ‚Â student services provided by the Social Sciences Faculty (FIS).Source of research data is the primary and secondary. A primary source is data obtainedÃ‚Â from the FIS service providers and students. Study sample as many as 96 people obtained byÃ‚Â snowball sampling technique and incidental sampling. Secondary data obtained from the databaseÃ‚Â of students, faculty profles, and SOP academic and student affairs. This research data collectedÃ‚Â through questionnaires, observation, interviews, and Focused Group Discussion (FGD). To testÃ‚Â the validity of data, used triangulation methods. Further data were analyzed quantitatively andÃ‚Â qualitatively.Ã‚Â From the results of research and feld fndings, it can be concluded the following things:Ã‚Â (1) academic and student services provided by the Social Sciences Faculty is in conformityÃ‚Â with principles, principles, and service standards as set by the government, (2) students andÃ‚Â stakeholders Other interests satisfed with the services provided by the Social Sciences Faculty, (3)Ã‚Â the general performance of the Faculty of Social services better, but in some service elements stillÃ‚Â need improvement, namely the responsibilities of staff, assurance / compliance costs of service,Ã‚Â speed of service, and certainty / precision service schedule. Based on our research, suggestedÃ‚Â the need for increased responsibility and speed of service by way of: (a) The unit leader shouldÃ‚Â coordinate and synchronize routine tasks, (b) the leadership of the faculty and administrationÃ‚Â (the administration) should do the monitoring and evaluation of staff performance or employees,Ã‚Â (c) the need for a refresher and increase staff competence in accordance with its tasks through